Implementasi Program Anti-dowry UN Women dalam Upayanya Mengatasi Permasalahan Dowry Death, India (2016-2021) - Syva Octaviani; Nur Azizah (Mahesa Research Center, 2023)
This article focuses on the anti-dowry program efforts carried out by UN Women in an effort to overcome the dowry problem in India. There are many cases of requests for dowry by grooms that are misused, causing women in India to experience discrimination and many deaths due to dowry or so-called dowry deaths. Therefore, United Nation Women as a UN entity that focuses on gender equality takes a role in contributing to dealing with dowry problems. This article aims to find out how international efforts, especially UN Women and the Non-Governmental Organization Corporation and Assistance for Relief Everywhere (CARE), have implemented the anti-dowry program which has been implemented since 2016-202 with a program focus in the fields of advocacy, education, economy and health. In order to approach this problem, the theory of feminism, the concept of human rights (HAM), and international organizations are used. This research was written using a qualitative descriptive method with secondary data source collection techniques using document analysis and library research. This study concludes that the anti-dowry program implemented can influence the reduction in the rate of gender discrimination and the number of deaths due to dowry in India.